2023
DOI: 10.1049/hve2.12319
|View full text |Cite
|
Sign up to set email alerts
|

Dissolved gas analysis and dissipation factor measurement of mineral oil‐based nanofluids under thermal and electrical faults

Abstract: Mineral oil is the most frequent insulating liquid used in oil‐immersed transformers for electrical insulation and heat dissipation. However, oil‐based nanofluids are becoming more popular in scientific research as they have proved to have better dielectric and thermal characteristics. When applying these nanofluids into actual transformers, they would be exposed to thermal and electrical stresses. Thus, The aim of the authors is to investigate the generation pattern of dissolved gases in nanofluids under ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Also, there are two O-Rings for preventing the evolved gases from escaping out of the vessel and the external gases from entering. Note that the clearance and creepage distances were taken into consideration during the design phase for minimising the risk of flashover [16,28].…”
Section: Test Cell Specificationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, there are two O-Rings for preventing the evolved gases from escaping out of the vessel and the external gases from entering. Note that the clearance and creepage distances were taken into consideration during the design phase for minimising the risk of flashover [16,28].…”
Section: Test Cell Specificationsmentioning
confidence: 99%
“…The underlying reason behind that returns to the pool boiling phenomenon that limits the temperature of the immersed heating element as reported in Refs. [28,30,31].…”
Section: Thermal Degradationmentioning
confidence: 99%
See 1 more Smart Citation
“…This parameter is the dissipation factor of the insulating liquid (tan δ ). A high value of the dissipation factor refers to the presence of more existing contaminations and imperfections in the insulating oil [ 31 , 32 ]. Therefore, mitigation of the dissipation factor value provides a positive impact on the insulation system.…”
Section: Oil Specifications and Experimental Proceedingsmentioning
confidence: 99%
“…The results showed that the addition of nanoparticles to mineral oil decreased the DDF after the presence of thermal and electrical faults. Thus, the presence of nanoparticles (such as SiO 2 , Al 2 O 3 , and TiO 2 ) inside the mineral oil increases its lifetime with better performance [ 27 ]. Abdali et al showed that the insertion of 0.01% weight percentage of diamond nanoparticles inside mineral oil can reduce the hotspot temperature to 5.1 °C and enhance the coolant properties of the mineral oil [ 28 ].…”
Section: Introductionmentioning
confidence: 99%